Making waves: how ultrasound-targeted drug delivery is changing pharmaceutical approaches. Issue 7 (3rd March 2022) - Delaney, Lauren J.; Isguven, Selin; Eisenbrey, John R.; Hickok, Noreen J.; Forsberg, Flemming
Abstract : A review article regarding ultrasound-triggered drug delivery, highlighting exciting clinical trials and new applications for this modality. Abstract : Administration of drugs through oral and intravenous routes is a mainstay of modern medicine, but this approach suffers from limitations associated with off-target side effects and narrow therapeutic windows. It is often apparent that a controlled delivery of drugs, either localized to a specific site or during a specific time, can increase efficacy and bypass problems with systemic toxicity and insufficient local availability. To overcome some of these issues, local delivery systems have been devised, but most are still restricted in terms of elution kinetics, duration, and temporal control. Ultrasound-targeted drug delivery offers a powerful approach to increase delivery, therapeutic efficacy, and temporal release of drugs ranging from chemotherapeutics to antibiotics. The use of ultrasound can focus on increasing tissue sensitivity to the drug or actually be a critical component of the drug delivery. The high spatial and temporal resolution of ultrasound enables precise location, targeting, and timing of drug delivery and tissue sensitization. Thus, this noninvasive, non-ionizing, and relatively inexpensive modality makes the implementation of ultrasound-mediated drug delivery a powerful method that can be readily translated into the clinical arena. This review covers key concepts and areas applied in the design of different ultrasound-mediated drug delivery systems across a variety of clinical applications.